2021
DOI: 10.1007/s10826-021-02200-1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Investigation into Pre- and Post-Natal Experience of Parents of Triplets

Abstract: Although parents of triplets experience substantial mental distress, research about this increasing population has primarily focused on physical health risks of triplets and mothers, failing to capture the subjective wellbeing of parents. Accordingly, this study aimed to understand first-hand experience of parents of triplets, using thematic analysis of semi-structured interviews participated by eight parents (four couples: Age M = 48.63, SD = 10.61 years). Six themes were identified: (1) Negative and (2) Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…The publication needed to include a form of intervention aimed at reducing parental stress. Systematic reviews, meta-analyses, randomised controlled trials, cohort studies, case studies, and qualitative studies were added to the inclusion criteria of this review as they are considered to be high-quality sources of evidence [33,34], as shown in the Hierarchy of Evidence Model [35].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The publication needed to include a form of intervention aimed at reducing parental stress. Systematic reviews, meta-analyses, randomised controlled trials, cohort studies, case studies, and qualitative studies were added to the inclusion criteria of this review as they are considered to be high-quality sources of evidence [33,34], as shown in the Hierarchy of Evidence Model [35].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Future research, such as a randomised control trial investigation into the effectiveness of compassion training for parents of children with ASD may show positive results in increasing compassionate parenting skills and practice. As outlined in the introduction, the benefits of this would be revealed through the empathic communication of a parent with their child and the alleviation of suffering or distress [ 23 ], thereby increasing quality of life as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Compassionate parenting has been broadly defined as an attempt by a parent or carer to see things through the eyes of the child and convey how the child is valued and understood [ 22 ]. This can be shown when a parent/carer engages and communicates empathically with their child and the sense of the child’s experience is considered with the intention of alleviating any suffering or distress the child might be experiencing [ 23 ]. A process where one is actively being kind and caring to one’s self, resulting in an expansion of the soothing system and reduction in suffering and sense of threat [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Merhametli ebeveynlik, bir ebeveyn veya bakıcının olayları çocuğun gözünden görme ve çocuğa nasıl değer verildiğini ve anlaşıldığını aktarma girişimi olarak tanımlanmaktadır (Kirby, 2020, s.2). Merhametli ebeveynlik, bir ebeveynin/bakımverenin çocuğuyla empatik bir şekilde ilişki ve iletişim kurması, çocuğun yaşadığı herhangi bir acıyı veya sıkıntıyı hafifletme niyetiyle eyleme geçmesi olarak açıklanabilmektedir (Kotera, Kaluzeviciute ve Bennett-Viliardos, 2022). Merhametli ebeveynlik açısından önem arz eden çeşitli becerilerden ve ilkelerden bahsedilmektedir: Şekil 1.…”
Section: Merhametli Ebeveynlik Tutumuunclassified